2013
DOI: 10.1371/journal.pone.0062549
|View full text |Cite
|
Sign up to set email alerts
|

Differential Virulence Gene Expression of Group A Streptococcus Serotype M3 in Response to Co-Culture with Moraxella catarrhalis

Abstract: Streptococcus pyogenes (group A Streptococcus, GAS) and Moraxella catarrhalis are important colonizers and (opportunistic) pathogens of the human respiratory tract. However, current knowledge regarding colonization and pathogenic potential of these two pathogens is based on work involving single bacterial species, even though the interplay between respiratory bacterial species is increasingly important in niche occupation and the development of disease. Therefore, to further define and understand polymicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…From the results it is noteworthy that in contrast to the infectious process of some other body systems, the URTI, particularly rhinosinusitis, ethmoiditis, rhinopharyngitis and adenoiditis most often (in more than 70% of cases) were with polymicrobial etiology. Similar results have also been reported in our earlier studies as well as other authors (3,4,13,14).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…From the results it is noteworthy that in contrast to the infectious process of some other body systems, the URTI, particularly rhinosinusitis, ethmoiditis, rhinopharyngitis and adenoiditis most often (in more than 70% of cases) were with polymicrobial etiology. Similar results have also been reported in our earlier studies as well as other authors (3,4,13,14).…”
Section: Discussionsupporting
confidence: 93%
“…This secondary infection is usually a bacterial one originating from the conditionally pathogenic microorganisms composing the normal colonizing flora of nasopharynx (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…As a consequence, gene expression in a pathogenic species is influenced by the presence of other pathogens as well as resident microflora within the host [ 7 ]. Some recent studies concerned with analyzing an individual pathogenic species gene expression in response to the presence of resident species in lung environment [ 56 , 7 ]. However there is a lack of comprehensive studies portraying the pattern of gene expression in the lung pathogenic species in the presence of other pathogenic strains in the lung environment.…”
Section: Discussionmentioning
confidence: 99%
“…Less common species recovered from patients presenting with symptoms of pharyngitis or with a clinical diagnosis of pharyngitis include Fusobacterium necrophorum ,21 described in a recent study as a true pathogen rather than a colonizer of the oropharynx,22 and the Streptococcus dysgalactiae subspecies equisimilis , which can cause severe or recurrent pharyngitis,3,17,23 although there is insufficient evidence of a role for S. dysgalactiae in other adverse outcomes 324 which may be significant considering that separate studies have demonstrated that M. catarrhalis potentiates the adhesion of S. pyogenes to the nasopharyngeal epithelium 25,26. Other bacteria cultured from patients with pharyngitis include Haemophilus influenza ,27 Arcanobacterium haemolyticum 28 and the opportunistic pathogen, Staphylococcus aureus , although the clinical significance of S. aureus association is not known 19…”
Section: Introductionmentioning
confidence: 99%